Carbon Nanotubes - Redefining the World of Electronics 2021
DOI: 10.5772/intechopen.94155
|View full text |Cite
|
Sign up to set email alerts
|

Carbon Nanotubes: Applications to Energy Storage Devices

Abstract: Carbon nanotubes (CNTs) are an extraordinary discovery in the area of science and technology. Engineering them properly holds the promise of opening new avenues for future development of many other materials for diverse applications. Carbon nanotubes have open structure and enriched chirality, which enable improvements the properties and performances of other materials when CNTs are incorporated in them. Energy storage systems have been using carbon nanotubes either as an additive to improve electronic conduct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 102 publications
(102 reference statements)
0
9
0
Order By: Relevance
“…CNTs have been used in energy storage systems such as alkali metal ion batteries [45], supercapacitors [46], and fuel cells [47]. CNTs are employed as an additive to boost electronic conductivity of cathode and anode materials in supercapacitors and fuel cells [48].…”
Section: Carbon Nanotubes (Cnts)mentioning
confidence: 99%
“…CNTs have been used in energy storage systems such as alkali metal ion batteries [45], supercapacitors [46], and fuel cells [47]. CNTs are employed as an additive to boost electronic conductivity of cathode and anode materials in supercapacitors and fuel cells [48].…”
Section: Carbon Nanotubes (Cnts)mentioning
confidence: 99%
“…Studies have shown that applying the CNTs as energy storage can improve the performance of electrochemical cells. It was determined that the variation of the lithium diffusion coefficient DLi with the activities of Li-ion in MWNTs electrodes was inversed (Amin, Kumar, & Belharouak, 2020).…”
Section: Energy Storagementioning
confidence: 99%
“…It is used as electrodes in supercapacitor and lithium ion batteries owing to its extraordinary tensile strength, electrical conductivity as well as ultrahigh surface region. Energy storage devices employ CNTs as additives in order to increase electrical conductivity of cathode and also as anode components [49,50].…”
Section: Energy Storage Applicationsmentioning
confidence: 99%